Pengendalian Urban Sprawl di Wilayah Pinggiran (Studi Kasus: Perkembangan Kota di Indonesia dan Perancis) - Ramlan, Nurazizah; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
The progress in urbanization within downtown areas has been expanded to the surrounding areas (i.e. periphery). This has been considered by the changes of the land uses in two geographically different countries. These areas have experienced a phenomenon of space consumption due to the urban development, which eventually triggered the urban sprawl, such as Mlati in Indonesia, Vertou, Caquefou and Sainte Luce Sur Loire in Nantes, France. This present study aims to examine the practices in the management of space consumption by urbanization in several municipals within periphery of Nantes, such as Carquefou, Sainte Luce sur Loire, Vertou and to compare with the sub-region of Mlati, in Sleman, Indonesia. The objective of this research was to answer the question; what are the major factors that influence the implementation of the policy controlling the urban sprawl in the periphery, in Indonesia and in France? These factors were decomposed in four components: regulations, institutions, resources and implementation. The approaches used in this study were, first of all, the quantitative method and based on its results. The second approach was done by descriptive qualitative method. The first approach was analysis of changes in land uses using evolution matrices of the change of land use, in order to study how a particular type of land use evolved and how it changed. The second step was done by an interview with the people key who are mastering the research subject, and then SWOT analysis was done from the interview. The results show that there is a significant difference between Indonesia and France, particularly in the human resources and implementation.